2022
DOI: 10.1097/mao.0000000000003703
|View full text |Cite
|
Sign up to set email alerts
|

Speech Recognition Performance Differences Between Precurved and Straight Electrode Arrays From a Single Manufacturer

Abstract: Objective: Precurved cochlear implant (CI) electrode arrays have demonstrated superior audiometric outcomes compared with straight electrodes in a handful of studies. However, previous comparisons have often failed to account for preoperative hearing and age. This study compares hearing outcomes for precurved and straight electrodes by a single manufacturer while controlling for these and other factors in a large cohort. Study Design: Retrospective cohort study. Setting: Tertiary academic medical center. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
(58 reference statements)
2
11
0
Order By: Relevance
“…Other studies have similarly shown equivalent long-term speech performance between precurved and straight electrodes, particularly after controlling for preoperative hearing and speech perception (35,36). Notably, previous comparisons of Cochlear electrodes have found superior postoperative CNC and AzBio scores with the precurved (CI532/632) over straight (CI422/522/622) electrode arrays (24,25). Variation from other device manufacturers could be related to the underlying signal processing and other device-specific factors as well as the Mid-Scala having a stylette and possibly being further from the modiolus than the CI532/632.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other studies have similarly shown equivalent long-term speech performance between precurved and straight electrodes, particularly after controlling for preoperative hearing and speech perception (35,36). Notably, previous comparisons of Cochlear electrodes have found superior postoperative CNC and AzBio scores with the precurved (CI532/632) over straight (CI422/522/622) electrode arrays (24,25). Variation from other device manufacturers could be related to the underlying signal processing and other device-specific factors as well as the Mid-Scala having a stylette and possibly being further from the modiolus than the CI532/632.…”
Section: Discussionmentioning
confidence: 94%
“…In hopes of better structural preservation, the precurved Mid-Scala electrode was designed for positioning within the middle of the scala tympani, ideally without contact with the modiolus or lateral wall. In the absence of scalar translocation and closer modiolar placement, precurved electrodes have been shown to successfully preserve hearing and have better speech outcomes than straight electrodes in some reports (24)(25)(26). Given the slightly varied goals of the Mid-Scala design, it is of interest to know whether the intended positioning near the middle of the scala tympani yields superior results to the lateral wall electrode array by the same manufacturer.…”
Section: Introductionmentioning
confidence: 99%
“…Although perimodiolar implants may lower SGN activation thresholds, they can cause more mechanical trauma (41). Two studies of normal cochleae demonstrated that patients with perimodiolar arrays had superior speech perception, although any advantage equalized by 2 years after insertion (38,42). Our current anatomical data are insufficient to support endorsement of one array over the other, and future work should model implant positions.…”
Section: Discussionmentioning
confidence: 99%
“…Although HP may be better with LW arrays, it is still often possible to preserve hearing with precurves designs (45,46). Recent studies have even shown similar rates of HP between PM and LW arrays (22,47). However, HP is multifactorial, with factors beyond electrode design under the surgeons' control.…”
Section: Do Arrays Differ In Hp?mentioning
confidence: 99%